Answer:
B) Since (-3,-2) does not satisfy both equations, it is not a solution to the
system.
Step-by-step explanation:
The given system of equations is:
[tex] {x}^{2} + {y}^{2} + x - 10y - 3 = 0[/tex]
[tex]x + y = - 4[/tex]
If (-3,-2) is a solution, then it must satisfy both equations:
Let us substitute into the first equation to get:
[tex] {( - 3)}^{2} + {( - 2)}^{2} + ( - 3) - 10( - 2) - 3 = 0[/tex]
Evaluate the exponents;
[tex]9 + 4 - 3 + 20- 3 = 0[/tex]
[tex]27 = 0[/tex]
This is not true
Also when we substitute into the scond equation, we get;
[tex] - 3 + - 2 = - 4 \\ - 5 = - 4[/tex]
This is also false.
Therefore the point is not a solution.